Remediation Program with Working Memory and Reading for Students with Learning Difficulties: Elaboration and Pilot Study - Isabella Nicolete Xavier; Simone Aparecida Capellini (Children)
Background/objectives: A child’s working memory needs to be efficient in order to perform well at school, because its manipulative function needs to work properly in order to compose and decompose words, a skill that is necessary for reading. Therefore, if a child with an alteration in this type of memory reads a more complex sentence, they will have difficulty storing it until other cognitive processes involved in language comprehension and production take place, leading to impaired reading comprehension. The aim of this study was to develop and verify the applicability of a remediation program for working memory and reading in students with learning difficulties from the third to fifth grades of primary school. Methods: The study was carried out in two phases: phase 1 developed the program on the basis of a literature review, and phase 2 verified the applicability of the program in a pilot study with 21 schoolchildren divided into two groups. The subjects were subjected to tests of metalinguistic and reading skills and the Brief Child Neuropsychological Assessment Instrument. Results: The working memory and reading remediation program consisted of 11 tasks developing phonological and visuospatial working memory. From the results of the application of the Remediation Program With Working Memory and Reading (RP-WMR) in a pilot study, it was possible to verify the applicability of the program; in other words, the strategies developed for students with learning difficulties can be generalised and applied to students who have deficits in working memory and reading. Conclusions: The result of this research indicates that the structured program for remediation of working memory difficulties has proven to be applicable and can help education professionals as a tool for intervening in working memory deficits and reading decoding skills presented by students with learning difficulties.